CEO’S PERSONALITY AND THEIR IMPACT ON AN ORGANIZATIONAL PERFORMANCE - Ciroka, Ndricim (European Scientific Journal, ESJ, 2014)
People have different personality. Personality differences in people are very important, because it determines the conditions for living and working together. From the perspective of business organizations, personality in general and that of the Chief Executive Officer (CEO) in particular has a significant increase because he/she is the leader of the organization. At this starting point, we want to present a theoretical approach of personality theories. We will be considering the integration of the Big 5 personality factors (Big Five) theory with the role of CEO’s personality, and their impact on the organizational performance. The CEO’s personality has a direct impact on an individual's behavior. It plays an important role in the group relations and interpersonal relations. It affects work motivation and job satisfaction, and as a whole, it reflects in the performance of the organization. Considering the Albanian business reality that began in the 90’s with a 20-year-old history and not having a very wide structure and relatively intense interpersonal relationships, the importance of the study of CEO’s personality became very important. Therefore, this paper emphasizes the importance of the personality theories, and the role of CEO’s personality in an organization.